2006
DOI: 10.1111/j.1478-4408.2006.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing of nylon 6 fabric with a new bifunctional vinyl sulphone reactive disperse dye

Abstract: A new bifunctional reactive disperse dye containing a temporarily anionic sulphatoethylsulphone and a nonionic disulphide bis(ethylsulphone) groups was synthesised and applied to nylon 6 fabric by the exhaust dyeing at a variety of pH and temperature conditions. A monofunctional reactive disperse dye containing only nonionic disulphide bis(ethylsulphone) group was also synthesised and its dyeing behaviour was compared with the bifunctional dye. The bifunctional reactive disperse dye exhibited high exhaustion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In general, reactive dyestuff will form a covalent bond with cellulose fibres only under alkali conditions, but printing nylon with reactive dyestuff requires a neutral or weakly acidic paste, as this allows the reactive dyestuff to combine with nylon and form a covalent bond [9,12]. This study used two different non‐volatile organic acids, citric acid and tartaric acid, as pH adjustment agents, investigating the same pH value (pH 5.5) and different types of acid agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, reactive dyestuff will form a covalent bond with cellulose fibres only under alkali conditions, but printing nylon with reactive dyestuff requires a neutral or weakly acidic paste, as this allows the reactive dyestuff to combine with nylon and form a covalent bond [9,12]. This study used two different non‐volatile organic acids, citric acid and tartaric acid, as pH adjustment agents, investigating the same pH value (pH 5.5) and different types of acid agent.…”
Section: Resultsmentioning
confidence: 99%
“…This article focuses on the ink‐jet printing of nylon fabric using reactive dyestuffs to determine the best conditions for forming the steady covalent bond between the amino group of nylon and the reactive dyestuffs, which does not require a serious fixing system, but achieves good wash fastness [5–7]. Although some studies [6,8–10] discuss dyeing or printing nylon fabric with a reactive dyestuff, they only use special reactive dyestuffs or colours for dyeing or printing with the traditional screen‐printing method and do not use ink‐jet printing of nylon with reactive ink. This study used four commercial reactive inks – cyan, magenta, yellow and black – for ink‐jet printing of nylon fabric.…”
Section: Introductionmentioning
confidence: 99%
“…Bathochromic shifts of the visible absorption band were observed on increasing the solvent polarity, where the difference in λmax was noticed upon measuring the dyes in ethanol, acetone and chloroform. This is of course expected for a system in which the excited state is more polar than the ground state [18,19,20). The effect of few drops of acids on ethanolic solution of the dyes was also observed and the results shows that dyes II 7 , II 8 , II 9 , II 10 and II 11 have positive halochromism as they absorbed maximally at 510, 437,415,505 and 483 respectively in a neutral solution of ethanol and absorb maximally at 471, 417, 412, 482 and 422 respectively in acidic of ethanol, indicating a bathochromic shift of +39, +20, +3, + 23 and +61 respectively.…”
Section: Visible Absorption Spectra Of the Dyesmentioning
confidence: 98%
“…Lee et al synthesized temporarily solubilized azo disperse dyes and reported dyeing properties on PET [11,12] and PET/cotton blends [13]. Youssef and Mousa researched about comparison between monofunctional and bifunctional SES reactivedisperse dyes on Nylon [14][15][16]. A reactive-disperse dye carrying acetoxyethylsulphone group was synthesized and applied to the dyeing of N/P mixture fabric [17].…”
Section: Introductionmentioning
confidence: 99%